PENONAKTIFAN 11 JUTA PESERTA PBI BPJS KESEHATAN BERDASARKAN UU NO. 40 TAHUN 2004 TENTANG SJSN PASAL 17 AYAT (4) DAN UU NO. 24 TAHUN 2011 TENTANG BPJS PASAL 11 HURUF C - Mutiara Hayulina Hidayah; Laila Ilmaghnum, Silsabilah; Rahmawati, Puji; Ali Baihaqi, Irfan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the legality, legal certainty, and implications of the simultaneous deactivation policy affecting approximately 11 million Health Contribution Assistance Recipients (PBI) of BPJS Kesehatan in early February 2026 based on the Decree of the Minister of Social Affairs Number 3/HUK/2026. This research employs a normative juridical approach examined through three analytical frameworks: the theory of statutory analysis, the theory of public welfare, and the public policy theory. The analysis focuses on the compliance of this administrative action with Article 17 Paragraph (4) of Law Number 40 of 2004 concerning the National Social Security System (SJSN) and Article 11 Letter c of Law Number 24 of 2011 concerning BPJS. The findings indicate that legally, the data updating and deactivation policy for participants who no longer meet the economic criteria can be justified as an implementation of BPJS's supervisory function to ensure targeted state budget efficiency. However, the execution of mass deactivation without adequate socialization, valid data accuracy, and a clear transition mechanism potentially violates citizens' constitutional rights to health security and social welfare. Therefore, the government and BPJS Kesehatan are obligated to provide re-verification procedures, easily accessible complaint mechanisms, and transparent participant reactivation systems to guarantee social justice and legal certainty for vulnerable groups.